The Relationship between Knowledge and the Role of Community Leaders on the Incidence of DHF - Deni Ardiansyah; Khoidar Amirus; Nova Muhani; Samino (Jurnal Penelitian Pendidikan IPA, 2023)
Lampung Province recorded 3,484 cases of Dengue Fever (DHF) or 435 cases in a month. Or there are 14 cases a day. South Lampung recorded 185 people who experienced DHF from January to August 2022. The purpose of this study was to determine the relationship between knowledge and the role of community leaders on the incidence of DHF in the working area of the Hajimena Health Center, South Lampung Regency in 2023. This type of research is quantitative with a cross sectional approach with a population of 96 respondents and the number of samples is the same as the population because it uses total sampling tectics because the population is less than 100 the entire population is sampled using univariate and bivariate analysis tests. To determine the frequency distribution of the dependent variable (DHF incidence) and to determine the relationship between the independent variables (knowledge and the role of community leaders). The results of univariate research are that there are 26 people who experience DHF, there are 55 respondents who have good knowledge and there are 42 respondents who have poor knowledge, and the role of community leaders is 65 respondents who play a good role and there are 32 respondents who do not play a good role. Bivariate results There is a significant relationship between the knowledge of community leaders on the incidence of DHF (pvalue = 0.011) and There is a significant relationship between the role of community leaders on the incidence of DHF (pvalue = 0.000) in the working area of the Hajimena Health Center in 2023. To improve the knowledge and role of community leaders in paying attention to the condition of the community environment and eradicating mosquito nests, support from health agencies such as health centers and health offices is needed.